The Efforts Of Islamic Religious Education Teachers In Developing The Intellectual Potential Of Students In The Learning Process - Silvia - Susrizal (Ruhama : Islamic Education Journal, 2021)
This research was conducted because of the need to develop intellectual potential in the learning process carried out by Islamic Religious Education teachers in SMP N 29 Padang. The purpose of this study is to determine the efforts made by Islamic Religious Education teachers to develop students' intellectual potential in improving the learning process. The research method used is descriptive field research. In this study PAI teachers have made efforts to develop students' intellectual potential, such as the provision of subject matter in accordance with the basic competencies to be achieved, giving students the task to improve students' memory and understanding of the material provided, recalling students' knowledge and insights, and deliver material using the lecture method, ask students to memorize lessons, give students the opportunity to discuss and present in front of the class, and the teacher uses the method of thinking in delivering the material.